Appreciating Prešeren's Wreath of sonnets" - Cooper, Henry R. (Slavistična revija, 2006)
This paper seeks to provide English-language readers with necessary background information about France Prešeren's "Wreath of Sonnets" (1834) so that they might more fully appreciate in the recent (1999) English translation the structural, thematic, and literary complexities of the Slovene original.
Keywords: Prešeren, Framce; prevodi v angleščino; rhyme; rhythm; rima; ritem; Slovene literature; Slovene poetry; slovenska književnost; slovenska poezija; Sonetni venec; translation into English